Mandibular nerve block in juvenile Nile crocodile: a cadaveric study. (November 2020) - Bianchi, Cristina; Adami, Chiara; Dirrig, Helen; Cuff, Andrew; d'Ovidio, Dario; Monticelli, Paolo
Abstract: Objective: To develop a technique for performing the mandibular nerve block in Nile crocodiles. Study design: Experimental cadaveric study. Animals: A total of 16 juvenile Nile crocodile heads. Methods: To study the course of the mandibular nerve, one head was dissected. Computed tomography (CT) examination was performed in two heads to identify useful landmarks. Thereafter, a hypodermic needle was inserted through the external mandibular fenestra of 17 hemimandibles (13 heads), and a mixture of methylene blue and iohexol was injected. Injection volumes were 0.5 ( n  = 7) and 1.0 mL ( n  = 10) for hemimandibles < 15 and ≥ 15 cm long, respectively. Iohexol spread and nerve staining with methylene blue were assessed with CT and anatomical dissection, respectively. Data were analysed with one-sample t test or Mann–Whitney U test. Significance was set at p < 0.05. Results: Both anatomical dissection and imaging confirmed the external mandibular fenestra as a useful anatomical landmark for needle insertion. The CT images acquired after needle positioning confirmed that its tip was located on the medial bony mandibular surface formed by the fusion of the angular and coronoid bones in 100% cases. In all the hemimandibles, the rostrocaudal spread of contrast was > 23 mm. The length of the stained mandibular nerve in the temporal region and of the stained medial branch of the mandibular nerve, as well as the dorsoventral and mediolateral spread of iohexol, was greater in group 1.0 than in group 0.5 ( p < 0.001). The caudal spread of iohexol was greater in group 1.0 than in group 0.5 ( p  = 0.01). Conclusions and clinical relevance: The technique developed in this study is feasible. Both injection volumes resulted in staining of the mandibular nerve. The spread of contrast in the anatomical region of interest may result in successful sensory block.